Konsentrasi Kepernilikan Media dan Ancaman Ruang Publik - - Eriyanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
The trend toward the concentration of media ownership in the hand of few media moguls in many parts of the world has been a subject of criticism. Concentration of media ownership has been one of the main threat to democracy and public sphere. This article discusses the concentration of media ownership in Indonesia and its consequences on democracy. One distinct picture of concentration of media ownership in Indonesia is that some of the owners of the media are politician. This article suggests that in order to tackle the problem there should be a limitation for media ouwnership especially for broadcasting and an effort to reestablish a more democratic media system by introducing public or community media.